Kegiatan Pelatihan Peningkatan Adversity Quotient (AQ) Bagi Usaha Kecil Dan Menengah (UKM) Kreatif Di Kota Bogor - Tyahya Whisnu H; Bayu Retno; Wasi Widayadi (FEB-UP Press, 2019)
Small and Medium Enterprises (SMEs) have been proven to make significant positive contributions to efforts to tackle economic and social problems in Bogor City. But in fact people with an entrepreneurial mindset alone are not enough to succeed because many are still unable to overcome the problem of adversity. Without a high advertisy quotient (AQ), it is feared that someone will experience frustration and setbacks in becoming an entrepreneur. For this reason, to solve the existing problems, the Adversity Quotient (AQ) Enhancement Training for Creative Small & Medium Enterprises (SMEs) is given. Adversity Quotient is intelligence to overcome difficulties.